1983
DOI: 10.2135/cropsci1983.0011183x002300040029x
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Genetic Parameters in Switchgrass1

Abstract: A population of switchgrass, Panicum virgatum L., consisting of 33 half‐sib families was investigated over 2 years to obtain estimates of genetic parameters for several agronomic and nutritive traits, including height, maturity, dry weight, in vitro dry matter disappearance (IVDMD), and percent N. Dry weight was less heritable than other traits, with an individual narrow‐sense heritability of only 0.25. Narrow‐sense heritability for dry weight calculated on a family mean basis was 0.59. Dry weight and IVDMD we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
71
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 0 publications
15
71
0
Order By: Relevance
“…For the SL-93 population, estimates of h 2 n (0.12 and 0.13 for PFM and individual plant selection, respectively) obtained from the progeny-parent regression method were considerably lower for both PFM and individual plant selection than those reported by Talbert et al (1983) in a lowland switchgrass population via estimation from variance component methods (0.59 and 0.25 for PFM and individual plant selection, respectively). This may be, in part, due to the progeny-parent regression method employed in elucidating estimates of h 2 n for the populations in this study, which tends to produce conservative estimates of h 2 n (Casler, 1982).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…For the SL-93 population, estimates of h 2 n (0.12 and 0.13 for PFM and individual plant selection, respectively) obtained from the progeny-parent regression method were considerably lower for both PFM and individual plant selection than those reported by Talbert et al (1983) in a lowland switchgrass population via estimation from variance component methods (0.59 and 0.25 for PFM and individual plant selection, respectively). This may be, in part, due to the progeny-parent regression method employed in elucidating estimates of h 2 n for the populations in this study, which tends to produce conservative estimates of h 2 n (Casler, 1982).…”
Section: Discussionmentioning
confidence: 69%
“…Switchgrass is allogamous and polymorphic with reported chromosome numbers ranging from 2n = 2x = 18 to 2n = 12x = 108 (Nielson, 1944;Henry & Taylor, 1989). Cross-pollination in the species is enforced by a gametophytic self-incompatibility system that is similar to the S-Z incompatibility system found in other Poaceae (Talbert et al, 1983;Martinè z-Reyna & Vogel, 2002;Taliaferro, 2002). All confirmed lowland ecotypes have been tetraploids (2n = 4x = 36) and most upland ecotypes are octoploids (2n = 8x = 72) .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Switchgrass is a highly heterozygous, self-incompatible and out-crossing species [41] with multiple ploidy levels ranging from 2n=2x=18 to 2n=12x=108 [3,7,33].…”
Section: Introductionmentioning
confidence: 99%
“…In most previous investigations researchers used heading date and/or flowering time to measure earliness versus lateness of reproductive development in switchgrass populations. Talbert et al (1983) and Van Esbroeck (1998) reported there was large genetic variation for flowering time in lowland switchgrass germplasm. Talbert et al (1983) reported high narrow-sense heritabilities (0.91 or above) for switchgrass maturity based on a lowland population of 33 half-sib families.…”
mentioning
confidence: 99%